Strategies of Islamic Religious Education Teachers in Facing the Challenges of Learning Digitalization at SMA 6 Persatuan Amal Bakti - Hasibuan, Riki Naldi (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2025)
This study aims to analyze the strategies of Islamic Religious Education teachers in facing the challenges of learning digitalization at SMA 6 Persatuan Amal Bakti. The development of digital technology provides both opportunities and challenges for the world of education, particularly in Islamic Religious Education subjects. This research employed a qualitative descriptive method with data collected through observation, interviews, and documentation. The findings reveal that Islamic Religious Education teachers apply various strategies, including the utilization of digital-based learning media, the improvement of digital literacy competence, the implementation of blended learning methods, and the use of contextual approaches to keep the learning materials relevant to students’ lives. The study concludes that the success of Islamic Religious Education learning in the digital era is strongly influenced by teachers’ creativity and adaptability in utilizing technology effectively.